The Influence of Corporate Governance and Audit Quality on Financial Performance with Earnings Management as a Mediating Variable (Case Study on Manufacturing Companies Listed on the IDX) - Siti Mariyah; Afrizal Afrizal; Netty Herawaty (Dhana, 2025)
This study aims to determine the effect of corporate governance and audit quality on financial performance with earnings management as a mediating variable. The population of this study is manufacturing companies listed on the IDX in 2020-2023. The sample of this study uses a purposive sampling technique with a total final sample of 175 manufacturing companies. This research method uses a quantitative method with secondary data in the form of company annual reports. The results of the study indicate that corporate governance has a positive effect on financial performance. Audit quality has a positive effect on financial performance. Earnings management has a positive effect on financial performance. Corporate governance has a negative effect on earnings management. Audit quality has a positive effect on earnings management. Earnings management is able to partially mediate the effect of corporate governance and audit quality on financial performance.